The Wnt7's Tale: A story of an orphan who finds her tie to a famous family. Issue 5 (7th April 2016) - Noda, Makoto; Vallon, Mario; Kuo, Calvin J.
Abstract : The transformation suppressor gene RECK was isolated by cDNA expression cloning (1998), and GPR124/TEM5 was detected as a tumor endothelial marker by differential screening (2000). The importance of Wnt7a/b and Gpr124 in brain angiogenesis was demonstrated by reverse genetics in mice (2008–2010). A series of recent studies using genetically engineered mice and zebrafish as well as luciferase reporter assays in cultured cells led to the discovery of functional interactions among Reck, Gpr124, and Wnt7a/b in triggering canonical Wnt signaling with relevance to embryonic brain angiogenesis and blood–brain barrier formation. Abstract : A series of recent studies using genetically engineered mice and zebrafish as well as luciferase reporter assay in cultured cells led to the discovery of functional interactions among Reck, Gpr124, and Wnt7a/b in triggering canonical Wnt signaling with relevance to embryonic brain angiogenesis.